THE DEVELOPMENT OF STUDENTS’ PERFORMANCE ASSESSMENT THROUGH SELF-ASSESSMENT TECHNIQUE - Hairida, Hairida; Ramlawati, Ramlawati (Unnes Science Education Journal, 2019)
This study aims to develop a performance assessment model through self-assessmenttechniques possible to measure students' science process skills in science-basedinquiry teaching learning process. The research used simplified design of Researchand Development from needs analysis, product development stage, and validation.Validation score indicates three aspects; usefulness 80%, model construction 83.33%,and readability model 81.67% all rated as very good criteria. In addition, the resultsof questionnaire about the implementation of the model obtained positive approvalfrom the users. The results show that the measurement model is uniquely useful tomeasure the student skills of science processing in a junior high school level.